2009
DOI: 10.1037/a0012967
|View full text |Cite
|
Sign up to set email alerts
|

Reactions to prejudicial statements: The influence of statement content and characteristics of the commenter.

Abstract: The purpose of this study was to examine factors that influenced the perceived offensiveness of a prejudicial comment. A mixed-methods study was conducted, with 134 college students participating. Results from a choice-based experiment indicated that racist comments were deemed more offensive than were sexist ones. These effects were amplified when the commenter was a prototypical perpetrator (i.e., when the commenter was White or male). Qualitative data collected from the participants also supported these fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…Results showed that women perceived a male but not a female leader displaying QB(-type) (vs. neutral) behavior as having less positive intent toward women, which in turn related to stronger attributions of sexism. This finding is consistent with research demonstrating that possible displays of sexism directed toward women are less likely to be noticed when the source of this behavior is a woman ( Baron et al, 1991 ; Barreto and Ellemers, 2005 ; Cunningham et al, 2009 ). This is the first research, however, to empirically demonstrate a similarity between QB(-type) behavior and sexism (which, as outlined before, are similar in behaviors but conceptually very different given their different underlying concerns or antecedents).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Results showed that women perceived a male but not a female leader displaying QB(-type) (vs. neutral) behavior as having less positive intent toward women, which in turn related to stronger attributions of sexism. This finding is consistent with research demonstrating that possible displays of sexism directed toward women are less likely to be noticed when the source of this behavior is a woman ( Baron et al, 1991 ; Barreto and Ellemers, 2005 ; Cunningham et al, 2009 ). This is the first research, however, to empirically demonstrate a similarity between QB(-type) behavior and sexism (which, as outlined before, are similar in behaviors but conceptually very different given their different underlying concerns or antecedents).…”
Section: Discussionsupporting
confidence: 91%
“…This lower skepticism follows from people tending to ascribe positive intent to someone expressing themselves negatively about their ingroup: They believe that the speaker intends to be constructive and means well ( Hornsey and Imani, 2004 ). Furthermore, an ingroup member would be a non-prototypical source of bias, and bias from a non-prototypical source (e.g., sexism from a female, racism from an ethnic minority) is less likely to be recognized as such ( Baron et al, 1991 ; Inman and Baron, 1996 ; Inman et al, 1998 ; Cunningham et al, 2009 ). Because of this non-prototypicality, behavior that would otherwise be perceived as negative might not necessarily be seen as such when the source of this behavior is an ingroup member.…”
Section: Introductionmentioning
confidence: 99%
“…Whether the relationship is congruent with prototypical expectations is especially crucial. “Most often, this entails a person with more power acting against a person or group with less power” (Cunningham, Ferreira, & Fink, , p. 60). Scholars recognize, however, that nonprototypical relationships may change the interpretation of nominally disparaging comments.…”
Section: The Role Of Words In Intergroup Relationsmentioning
confidence: 99%
“…Motives matter. Because some observers may assume that a member of the disparaged group would not make disparaging comments about her or his own group (Cunningham et al, , p. 61), they conclude that seeming slurs must not have been intended to be disparaging. Just as in so many areas of law (e.g., criminal assault, hate crimes), perceived intentions provide a context for interpreting actions.…”
Section: The Role Of Words In Intergroup Relationsmentioning
confidence: 99%
“…Previous research has also shown that the same statement is deemed to be more offensive when it is made by an individual who might be expected to be in a more dominant position (Baron et al, 1991;Cunningham et al, 2009). However, to the best of our knowledge, it has never been shown that, under some specific conditions, people who make offensive statements are deemed more dominant.…”
mentioning
confidence: 82%